PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GAME ROLE PLAYING GAME (RPG) PADA MATERI SISTEM KOMPUTER KELAS X MANAGEMEN PERKANTORAN 2 SMK PGRI 1 TULUNGAGUNG - Syaifudin Zuhri, Muhammad; Dwi Pamungkas, Bian; Panggayuh, Vertika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low interest and involvement of students in Computer Systems learning materials due to the use of less interesting media and difficulties in visualizing abstract concepts. This study aims to develop a Role Playing Game (RPG)-based learning media on Computer Systems material for class X MP 2 SMK PGRI 1 Tulungagung and determine its feasibility level. The method used is Research and Development (R&D) with the ADDIE model which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The product was developed using Construct 2 in the form of an Android application (.apk). Data collection techniques used observation, interviews, and questionnaires. The results of the study showed that the developed media obtained a media expert validation percentage of 96.43%, material expert validation of 100%, and large group trial results of 97.93%, so that RPG-based learning media was declared very suitable for use as an alternative learning media that is interactive, interesting, and supports more effective learning.